4-Nitrophenol (PNP) inhibits the expression of estrogen receptor β and disrupts steroidogenesis during the ovarian development in female rats. (October 2017) - Zhang, Haolin; Taya, Kazuyoshi; Nagaoka, Kentaro; Yoshida, Midori; Watanabe, Gen
Abstract: 4-nitrophenol (PNP), isolated from diesel exhaust particles, has estrogenic and anti-androgenic activities, and affects the hypothalamus-pituitary-gonad axis in male rats. However, the effect of PNP on the reproduction of the female rats is still unknown. The aim of the study was to investigate the effect of neonatal PNP exposure on the ovarian function of female rats. The neonatal female rats were exposed to PNP (10 mg/kg, subcutaneously injection), the ovary and serum samples were collected at postnatal day (PND) 7, 14 and 21. The results showed that the ratio of primordial and primary follicles increased whereas the ratio of antral follicles decreased in the PNP treated ovaries at PND21. Even though no abnormality was observed in cyclicity, there was a significantly delayed timing of vaginal opening in PNP treated rats. The ovarian expression of steroidogenic enzymes including StAR, P450scc, P450c17 and P450arom increased at PND14 in the PNP treated rats compared with the control rats. In consistent with the gene expression, the concentration of estradiol-17β showed the similar pattern. However, PNP exposure failed to cause any significant change in the expression of steroidogenic enzymes in cultured neonatal ovaries. Furthermore, PNP suppressed the expression of estrogen receptor β (ERβ), but not estrogen receptor α (ERα), in cultured ovaries or developmental ovaries. These results suggested that PNP might directly affect the expression of ERβ in the rat ovaries, resulting in the disrupted steroidogenesis during ovarian development and the delayed puberty. Graphical abstract: Highlights: Neonatal exposure to 4-nitrophenol delayed follicle development and vaginal opening. Neonatal exposure to 4-nitrophenol elevated ovarian steroidogenesis at PND14. Neonatal exposure to 4-nitrophenol directly suppressed ERβ expression in the ovary.